H i filaments as potential compass needles? Comparing the magnetic field structure of the Small Magellanic Cloud to the orientation of GASKAP-H i filaments. Issue 1 (14th February 2023) - Ma, Y K; McClure-Griffiths, N M; Clark, S E; Gibson, S J; van Loon, J Th; Soler, J D; Putman, M E; Dickey, J M; Lee, M -Y; Jameson, K E; Uscanga, L; Dempsey, J; et al.
ABSTRACT: High-spatial-resolution H i observations have led to the realization that the nearby (within few hundreds of parsecs) Galactic atomic filamentary structures are aligned with the ambient magnetic field. Enabled by the high-quality data from the Australian Square Kilometre Array Pathfinder ( ASKAP ) radio telescope for the Galactic ASKAP H i survey, we investigate the potential magnetic alignment of the $\gtrsim\!{10}\, {\rm pc}$ -scale H i filaments in the Small Magellanic Cloud (SMC). Using the Rolling Hough Transform technique that automatically identifies filamentary structures, combined with our newly devised ray-tracing algorithm that compares the H i and starlight polarization data, we find that the H i filaments in the north-eastern end of the SMC main body ('Bar' region) and the transition area between the main body and the tidal feature ('Wing' region) appear preferentially aligned with the magnetic field traced by starlight polarization. Meanwhile, the remaining SMC volume lacks starlight polarization data of sufficient quality to draw any conclusions. This suggests for the first time that filamentary H i structures can be magnetically aligned across a large spatial volume ($\gtrsim\!{\rm kpc}$ ) outside of the Milky Way. In addition, we generate maps of the preferred orientation of H i filaments throughout the entire SMC, revealing the highly complex gaseous structures of the galaxy likely shaped by a combination of the intrinsic internal gas dynamics, tidal interactions, and star-formation feedback processes. These maps can further be compared with future measurements of the magnetic structures in other regions of the SMC.